Polycythaemia rubra vera and hairy cell leukaemia in the same patient: studies on the spleen. Issue 12 (December 1982) - Mufti, GJ; Hamblin, TJ; Stevenson, FK; Fitchett, M
Abstract : The first association of polycythaemia rubra vera (PRV) and hairy cell leukaemia (HCL) is reported. The secretion by spleen cells in short term culture of IfGλ to the exclusion κ demonstrated that despite aberrant surface marker studies the HCL was a monoclonal tumour of B cells. Chromosomal studies on splenic cells were not able to demonstrate the common clonal origin of the two tumours.